AB0491 Pleural and Pulmonary Involvements in Systemic Lupus Erythematous. (15th July 2016) - Ben Salem, T.; Naceur, I.; Tougorti, M.; Lamloum, M.; Khanfir, M.; Ben Ghorbel, I.; Houman, M.H.
Abstract : Background: Pleural and pulmonary involvements (PPI) occur in almost half of the patients with systemic lupus erythematous (SLE). The aim of the study was to determine prevalence of these manifestations in a group of Tunisian SLE patients and to describe their clinical, biological, and immunological characteristics. Methods: We conducted a retrospective study of patients who fulfilled the revised ACR criteria of SLE admitted in an Internal Medicine department over a period time of 14 years. Patients with PPI related to SLE were included. Infectious states were excluded. Respiratory involvements were evaluated using chest x-ray, computed tomography (CT) and pulmonary function tests. Results: Sixty six SLE patients had PPI (27%). The mean age was 36 years (ranges 14 to 69 years). The sex-ratio M/F was 0.1. Clinical symptoms were dyspnea (6 cases), chest pain (4 cases) and fever (32 cases). The chest X-Ray was abnormal in 66 cases: pleural effusion (n=65), atelectasis (n=2) and parenchymal opacities (n=1). CT showed parenchymal bands in three cases and fluctuating multifocal opacities in one patient. Pleural fluid was lymphocytic in all cases. Pulmonary function tests showed restrictive syndrome in two cases. PPI was found in 44 cases (67%) at the time of SLE diagnosis and revealed the disease in 18 cases. In other cases, PPI occurred after mean disease duration of 44 months. Pleural effusion was confirmed in 65 patients. Two patients had Shrinking syndrome. Bronchiolitis obliterans was diagnosed in one patients and organizing pneumonia in another one. Pulmonary hypertension was noted in 4 patients. Other involvements were noted in all patients: pericardial effusion (77%), cutaneaous manifestations (74%), lupus nephritis (36%), neurological involvements (14%) and myositis (9%). Comparison of patients with and without PPI involvements showed that pericarditis was significantly more frequent in patients with PPI (76.2% vs 22.6%; p<0.001). Antibodies to extractable antigens and anti-SSB/La antibodies were more frequent in these patients (94% vs 82.6%; p=0.049 and 57.9% vs 28.4%; p=0.001 respectively). Patients received steroids and immunosuppressant drugs in 88% and 51% of cases respectively. Pleural effusion was recurrent in 7 patients. Mean duration of follow up was 69 months (range 0–187). Conclusions: SLE had a wide spectrum pulmonary manifestations; pleural effusion is the most frequent. PPI can be due to lupus itself or to other associated conditions. In all cases, possible infectious and drug-induced causes should be ruled out. Disclosure of Interest: None declared